2015
DOI: 10.1590/s0100-736x2015000100017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the estrous cycle in Galea spixii(Wagler, 1831)

Abstract: RESUMO.-[Caracterização do ciclo estral de Galea spixii (Wagler, 1831).]Os Galea spixii habitam a vegetação semiá-rida da Caatinga, no Nordeste brasileiro. Eles são criados em cativeiro para realização de pesquisas relacionadas a biologia da reprodução. Sendo assim, o objetivo deste trabalho foi caracterizar o ciclo estral de G. spixii para obtenção de informações que melhorem o conhecimento do manejo reprodutivo da espécie em cativeiro. O ciclo estral foi monitorado por citologia esfoliativa vaginal em doze f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 20 publications
(44 reference statements)
2
30
0
6
Order By: Relevance
“…In our previous studies, polyestrous cycles of females lasting 14-19 days (Santos et al, 2015) with development of vaginal closure membrane (Santos et al, 2014a) were found. In other study, cytochrome enzymes P450c17 and P450 aromatase were found in vaginal tissue throughout estrous cycle suggesting a local production of androgen and estrogen hormones (Santos et al, 2014b) in agreement with several studies that have shown a wide variety of different production sites of steroid hormones in different mammalian species (Conley and Hinshelwood, 2001;Conley et al, 2004).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…In our previous studies, polyestrous cycles of females lasting 14-19 days (Santos et al, 2015) with development of vaginal closure membrane (Santos et al, 2014a) were found. In other study, cytochrome enzymes P450c17 and P450 aromatase were found in vaginal tissue throughout estrous cycle suggesting a local production of androgen and estrogen hormones (Santos et al, 2014b) in agreement with several studies that have shown a wide variety of different production sites of steroid hormones in different mammalian species (Conley and Hinshelwood, 2001;Conley et al, 2004).…”
Section: Introductionmentioning
confidence: 76%
“…It is found in semiarid to arid climate region of Brazilian Northeastern (Oliveira et al, 2008) where it is constantly used as an alternative source of protein for inhabitants of this region. For this reason, it is bred in captivity to provide alternative food, preserve the species and to development of a new experimental model (Santos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, female presents uterine tubes, uterus and two uterine horns with glands, which open into a single cervix, connecting with the vagina through the fornix, and a vulva with a clitoris pierced by the urethra. As a peculiarity, females do not present a vaginal vestibule, but a vaginal occlusion membrane is present (Santos et al, 2015). The female reaches sexual maturity at 55-90 days on average (Larcher, 1981), presenting a continuous poliestric cycle with a mean duration of 15.8 ± 1.4 days (Santos et al, 2015).…”
Section: Reproductive Aspectsmentioning
confidence: 99%
“…As a peculiarity, females do not present a vaginal vestibule, but a vaginal occlusion membrane is present (Santos et al, 2015). The female reaches sexual maturity at 55-90 days on average (Larcher, 1981), presenting a continuous poliestric cycle with a mean duration of 15.8 ± 1.4 days (Santos et al, 2015). The estrus can lasts from 6 to 11 days, and the predominance of cornified superficial epithelial cells can be highlighted through the vaginal cytological examination (Santos et al, 2015), associated to the presence of preovulatory follicles in the ovaries (Santos et al, 2017).…”
Section: Reproductive Aspectsmentioning
confidence: 99%
See 1 more Smart Citation